A morphometric study of the endoplasmic reticulum in human hepatocytes: Correlation between morphological and biochemical data in subjects under treatment with certain drugs. Issue 9 (September 1974) - Jézéquel, A. M.; Koch, M.; Orlandi, F.
Abstract : The distribution of the endoplasmic reticulum in human hepatocytes is defined in quantitative terms using the techniques of morphometry. The subjects of the study are liver biopsies from normal, untreated subjects and patients being treated with various drugs. In contrast to rat hepatocytes, the amount of smooth endoplasmic reticulum (SER) in man exceeds that of the rough endoplasmic reticulum (RER) and accounts for 76·3% of the total endoplasmic reticulum. This is to be taken into consideration in pharmacological or toxicological studies. In addition, two components of the SER have been identified: more prominent is the type 1 or vesicular which has a regular honeycomb pattern, made up of cisternae with patent lumina and a mean width of 1500 A; the type 2, or non-vesicular, occurs in discrete foci of densely packed smooth membranes with a spacing of about 140 A. In subjects under short-term treatment with Benzodiazepin (diazepam) the RER remained unchanged but the SER membranes were significantly increased with a remarkable, two-to threefold increase of the SER type 2 in three out of four patients. A rise in incorporation of 14 C-acetate into digitonin-precipitable sterols as measured in liver biopsy material was also noted in these three patients. The suggestion is made that the SER 2 represents the newly formed membranes whereas the SER 1 would represent `adult' membranes. No changes were observed in two patients under short-term treatment with phenobarbital or Dilantin.